Probing Gluons with the Future Spin Physics Detector - Alexey Guskov; Amaresh Datta; Anton Karpishkov; Igor Denisenko; Vladimir Saleev (Physics, 2023)
In this paper, we review the physics studies to be performed with the Spin Physics Detector (SPD) at the Nuclotron-based Ion Collider fAcility (NICA) which is a multi-purpose experiment designed to study nucleon spin structure in the three dimensions. With capabilities to collide polarized protons and deuterons with center-of-mass energy up to 27 GeV and luminosity up to <semantics>1032<mspace width="3.33333pt"></mspace>cm−2<mspace width="4pt"></mspace>s−1</semantics> for protons (an order of magnitude less for deuterons), the experiment is considered to allow measurements of cross-sections and spin asymmetries of hadronic processes sensitive to the unpolarized and various polarized (helicity, Sivers, Boer-Mulders) gluon distributions inside the nucleons. Results from the SPD will be complimentary to the present high-energy spin experiments at the RHIC (Relativistic Heavy Ion Collider) facility or future experiments such as the Electron-Ion Collider (EIC) at BNL (Brookhaven National Laboratory) and the AFTER experiment at the LHC (Large Hadron Collider) in understanding the spin structure of the basic building blocks of visible matter. Monte Carlo simulation-based results presented here demonstrate the impact of the SPD asymmetry measurements on gluon helicity parton distribution function (PDF) and gluon Sivers functions. With polarized deuteron collisions, the SPD is expected to be the unique laboratory for probing tensor-polarized gluon distributions. Additionally, there are possibilities of colliding other light nuclei, such as carbon, at reduced collision energy and luminosity during the first stage of the experiment.